2014
DOI: 10.1007/s00127-014-0914-0
|View full text |Cite
|
Sign up to set email alerts
|

From adversity to psychosis: pathways and mechanisms from specific adversities to specific symptoms

Abstract: Few studies have considered symptoms, underlying mechanisms and different kinds of adversity at the same time. Future research along these lines will have the potential to elucidate the mechanisms that lead to severe mental illness, and may have considerable clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
227
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(250 citation statements)
references
References 156 publications
16
227
1
6
Order By: Relevance
“…These findings add further weight to the suggestion that there may be distinct pathways from specific forms of CA to particular types of psychotic symptoms (Bentall et al 2014) and these warrant further investigation. In terms of clinical implications, our findings reiterate the need for a history of childhood adversity to be taken during routine psychiatric assessments of individuals presenting with psychosis in order to facilitate meaningful and comprehensive treatment plans (Read & Bentall, 2012).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…These findings add further weight to the suggestion that there may be distinct pathways from specific forms of CA to particular types of psychotic symptoms (Bentall et al 2014) and these warrant further investigation. In terms of clinical implications, our findings reiterate the need for a history of childhood adversity to be taken during routine psychiatric assessments of individuals presenting with psychosis in order to facilitate meaningful and comprehensive treatment plans (Read & Bentall, 2012).…”
Section: Resultssupporting
confidence: 52%
“…Given previous research that has explored associations between CA and individual symptoms of psychosis and schizotypy, we hypothesised that all forms of CA would be associated with the positive dimension (Read et al 2003;Janssen et al 2004;Whitfield et al 2005;Schürhoff et al 2009;Bentall et al 2012;Stilo et al 2013;Velikonja et al 2015). As there is a consistent body of literature linking CSA with depression (e.g., Bifulco et al 1991;Kendler & Aggen, 2014;Sitko et al 2014) we also hypothesised that this type of CA would be associated with the depressed symptom dimension.…”
Section: Introductionmentioning
confidence: 90%
“…This is in line with a recent meta-analytic review (Vonderlin et al, 2018) that also found CSA to be especially strongly related to dissociation, when compared to neglect and emotional abuse. CSA has also been identified as a potent risk factor for auditory hallucinations (Bentall et al, 2014), which are conceptualized as a symptom of TRASC in the 4-D model. Furthermore, higher reporting of childhood emotional neglect emerged as the only significant difference between patients with and without CDD comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of studies has reported direct correlations between voice hearing and trauma (see Bentall et al, 2014). In a review, McCarthy-Jones (2011) reported that child sexual abuse predicted a two-fold risk of voice hearing and a six-fold risk of commenting/commanding voices.…”
Section: The Relationship Between Trauma and Voice Hearingmentioning
confidence: 99%
“…But, at its more extreme end, this continuum may involve externalising biases (i.e. misattributions of internal events to external sources; Allen, Aleman, & McGuire, 2007;Bentall et al, 2014).…”
Section: Pathways To Voice Hearingmentioning
confidence: 99%